انتشار الإرضاع الوالدي الحصري والعوامل المرافقة عند أمهات الرضع المراجعين لمشفى تشرين الجامعي في اللاذقية:دراسة مقطعية عرضانية - زاهر محمد; متوج محمد; اسماعيل ريم (Latakia University Journal -Medical Sciences Series, 2018)
Objective: Determination of the prevalence of exclusive breastfeeding among mothers of infants who visited the children section and clinic of Tishreen University Hospital in Latakia, and studying the effect of some factors associated with exclusive breastfeeding: mother’s age, mother’s work, mother’s education, mother’s smoking, place of residence,family income, Infant gender, Infant birth weight, , gestational age, being afirst baby of the family, Parity, infant’s hospitalization during the first month of life, type of delivery, putting the baby on the breast during the first hour after delivery, Prelacteal feeding, receiving medical advice, and the existence of false beliefs about breastfeeding Methods:T he sample of the study included 450 infants of mothers who visited the children section and clinic of Tishreen University Hospital in Latakia,who aged between six months and two years from the beginning of June 2016 until June 2017 The mothers were interviewed face to face . a Prepared questionnaire was filled for each mother after taking her permission. Various socio-demographic variables, obstetric and infant factors, and breastfeeding practices were assessed for any influence on exclusive breastfeeding. Results: Only 59.3% of infants were exclusively breastfed at the age of 6 months. Chi-Square test revealed that the factors wich were negatively associated with exclusive breastfeeding were : unsatisfactory family income(p=0.001) , low birth weight (p =0.011) mother’s work (p =0.05), cesarean delivery (p =0.045) , infant’s hospitalization during the first month of life(p=0.01), not putting the baby on the breast during the first hour after delivery(p=0.048) , giving Prelacteal feed (p=0.01) هدف الدراسة: تحديد نسبة انتشار الإرضاع الوالدي الحصري بين أمهات الرضع المراجعين لعيادة وقسم الأطفال في مشفى تشرين الجامعي في اللاذقية،ودراسة تأثير بعض العوامل المرافقة على خيار الإرضاع الوالدي الحصري : وهي عمر الأم ,عمل الأم ,مستوى تعليم الأم ,تدخين الأم ,مكان الإقامة ,دخل الأسرة الشهري, جنس الرضيع, وزن ولادة الرضيع, العمر الحملي ,ترتيب الطفل, الإنجابية, وجود استشفاء في شعبة الحواضن خلال الشهر الأول بعد الولادة ,طريقة الولادة, وضع الرضيع على الثدي خلال الساعة الأولى بعد الولادة، إعطاء أغذية أخرى قبل اللبأ كالماء المحلى أو غيره، تلقي النصح الطبي، ووجود اعتقادات خاطئة عند الأهل حول الإرضاع الوالدي طريقة البحث والمرضى: شملت عينة الدراسة 450 رضيعا من أطفال الأمهات المراجعات لعيادة وقسم الأطفال في مشفى تشرين الجامعي باللاذقية ممن تتراوح أعمارهم بين ستة أشهر وسنتين منذ بداية حزيران 2016حتى حزيران 2017 أجريت المقابلات مع الأمهات وجهاً لوجه وتم ملء استمارة استبيانية معدة سلفاً لكل أم بعد أخذ موافقتها، تم تقييم مختلف المتغيرات الاجتماعية الديموغرافية، العوامل التوليدية و العوامل المتعلقة بالرضيع، وممارسات الرضاعة الطبيعية لمعرفة أثرها على على الإرضاع الوالدي الحصري . النتائج فقط 59.3% من الرضع كانوا يرضعون إرضاعاً والدياً حصرياً بعمر الستة أشهر .اختبار كاي مربع بين أن العوامل المرتبطة بشكل سلبي بالإرضاع الوالدي الحصري كانت الدخل الشهري غير الكاف (p=0.001)،وزن الولادة المنخفض(p=0.011)،الولادة القيصرية (p=0.045)، استشفاء الرضيع في شعبة الحواضن بالشهر الأول بعد الولادة (p=0.01)،عمل الأم (p=0.05)،عدم وضع الرضيع على الثدي بالساعة الأولى بعد الولادة(p=0.048)،و إعطاء أغذية أخرى للرضيع قبل اللبأ كالماء المحلى بالسكر و غيره (p=0.01)